Cross-cultural examination of a product of differing familiarity (Hard Cider) by American and Chinese panelists using rapid profiling techniques. (January 2020) - Jamir, Sierra Mari R.; Stelick, Alina; Dando, Robin
Highlights: Hard cider was evaluated by Chinese and American panelists, using rapid profiling. More, and more nuanced terms were generated by American than Chinese panelists. Abstract: Alcoholic cider is one of the fastest growing beverage categories in the US, with consumption increasing many fold in the last decade. This study investigates the cultural differences in characterization of craft and commercial hard ciders between American and Chinese consumers. Two untrained panels assessed their perception of hard cider samples (two commercial, five craft hard ciders, one additional blind duplicate craft cider) through free multiple sorting (FMS), and flash profiling (FP). A multiple factor analysis for FMS and General Procrustes Analysis for FP showed that the sensory maps produced by the groups showed some similarity, however more variability was evident in the Chinese group. Critically, the American group employed more nuanced descriptors for aroma and flavor (e.g. nutty, onion, oxidized, robustness, yeasty ) and describing complex mouthfeel attributes (e.g. carbonation, viscosity, and roughening ). American panelists also used 40% more terms than Chinese panelists, who used mostly basic flavors, tastes, hedonic terms, and comparisons to describe varying sensory experiences. A lack of exposure to hard ciders in the Chinese group, combined with linguistic differences, and a lack of standardized lexicon for ciders could contribute to less discriminability perceived between products. Our results highlight the importance of considering cultural and language differences, along with familiarity with the product category of interest in comparative cross-cultural work. Understanding these cultural differences to conduct cross-cultural sensory research may be of great importance to cider makers as the industry moves towards developing a standardized vocabulary for hard cider evaluation.